2019
DOI: 10.3390/cells8111441
|View full text |Cite
|
Sign up to set email alerts
|

Licochalcone A-Induced Apoptosis Through the Activation of p38MAPK Pathway Mediated Mitochondrial Pathways of Apoptosis in Human Osteosarcoma Cells In Vitro and In Vivo

Abstract: Background: Licochalcone A (LicA) is isolated from the roots of Glycyrrhiza glabra and possesses antitumor and anti-invasive activities against several tumor cells. However, the antitumor effects of LicA on human osteosarcoma cells have yet to be demonstrated either in vitro or in vivo. Methods: Cell viability was measured by MTT assay. Apoptosis and mitochondrial dysfunction were detected with Annexin V/PI staining and JC-1 staining by flow cytometry. The expressions of caspase- or mitochondrial-related prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…Cell culture was performed as described in a previous study [ 41 ]. Human 143-B and HOS osteosarcoma cell lines were kindly provided by Prof. Shun-Fa Yang (Institute of Medicine, Chung Shan Medical University, Taichung, Taiwan).…”
Section: Methodsmentioning
confidence: 99%
“…Cell culture was performed as described in a previous study [ 41 ]. Human 143-B and HOS osteosarcoma cell lines were kindly provided by Prof. Shun-Fa Yang (Institute of Medicine, Chung Shan Medical University, Taichung, Taiwan).…”
Section: Methodsmentioning
confidence: 99%
“…High levels of radiation cause excessive activation of PARP-1, and this high level of PARP-1 can activate release of apoptosis-inducing factor (AIF). AIF is transferred from the cytoplasm to the nucleus and can promote DNA fragmentation and chromatin aggregation in the nucleus, resulting in apoptosis [37,38].…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…Other findings have demonstrated that calycosin can inhibit growth and induce apoptosis in breast cancer cells via estrogen receptor β-dependent regulation of the insulin-like growth factor 1 receptor, p38 MaPK and Pi3K/akt pathways in breast cancer cells (15). In vitro and in vivo research demonstrated that licochalcone a regulated the mitochondrial-mediated internal apoptotic pathway via p38-MaPK, and exerted antitumor effects on human osteosarcoma cells (28). Similarly, the present study suggested that calycosin increased p-p38-MaPK expression, whereas a specific p38 inhibitor, BIRB 796, significantly reversed the effects of calycosin treatment on the viability, caspase expression, MMP and apoptotic rate of osteosarcoma 143B cells.…”
Section: Discussionmentioning
confidence: 97%
“…The role of p38-MAPK in cell proliferation and apoptosis has been extensively investigated ( 27 ). Accumulating evidence has suggested that the role of p38-MAPK is controversial in several tumor cells, and the variation may be associated with the applied stimuli and duration, as well as the specific characteristics and types of cells ( 28 ). The evidence revealed that NK007 induces G1/S cell cycle arrest by promoting p38-MAPK phosphorylation and suppressing the expression of hexokinase2, which is associated with acidification and oxygen consumption in ovarian cells ( 29 ).…”
Section: Discussionmentioning
confidence: 99%